Lot-sizing policies for defective and deteriorating items with time-dependent demand and trade credit. (2017) - Tiwari, Sunil; Wee, Hui-Ming; Sarkar, Sumon
This study investigates an inventory model with unreliable supply where each received lot may have random fraction of defective items with known distribution. Thus, item inspection becomes essential in all the situations, especially when the items are of deteriorating nature. Moreover, in today's competitive business world, organisations may use promotional tools in order to increase their sales. One such tool is permissible delay in payments where the buyer does not have to pay for the goods purchased until a prescribed period given by the supplier. For the case when both the demand and the price vary with time, we investigate the impact on the retailer's ordering policy for deteriorating items under permissible delay in payments. Numerical examples and sensitivity analysis are illustrated to provide some important managerial implications. [Received 26 December 2016; Revised 20 April 2017; Revised 5 June 2017; Revised 3 July 2017; Accepted 11 July 2017]